Teacher Strategies in Teaching Listening During Online Classes: Strategi Guru di Pengajaran Mendengarkan Selama Kelas Online - Mubarrok, M Miftakhul; Taufiq, Wahyu (Indonesian Journal of Education Methods Development, 2021)
This research discusses the teacher’s strategies in teaching listening at a Vocational High School in Indonesia during online class. The aims of the research are to know the strategies teacher in teaching listening and how the implementation of those strategies especially in situation which online class must be conducted in a Vocational High School in East java, Indonesia. The method used by the researchers is descriptive qualitative research method. The subject of the research is the English teacher in the Vocational High School while the methods of data collection were Observation checklist, interview guidline, and documentation. The data analysis techniques used data collection and documentation. The result of this study indicates that the teaching strategies used by the teacher was Planning, Monitoring, Evaluating, Cognitive, Metacognitive. The implementation of teacher strategies was the teacher looked at the syllabus with the lesson plan, material to teach in the lesson plan must match the class to be taught, the instructions in the listening learning process, then the teacher played the video in learning process. Hopefully, this study might be useful for other researchers as well as teachers who teach English in general and listening in particular.